An Investigation of the Role of an On-Site Library in the Provision of Adjunct Bibliotherapeutic Treatment for Emotionally Disturbed Youth - Battleson, Brenda; Nesset, Valerie (Qualitative and Quantitative Methods in Libraries, 2017)
Using a mixed methods approach, this three-phase research study will investigate the role of a professionally staffed, on-site library in the treatment of emotionally disturbed children and adolescents who are residents of an intermediate care in-patient treatment facility in Upstate New York, U.S.A. At the present time, there are no professionally staffed libraries in any such facility in New York State so this three-phase exploratory study aims to fill some gaps in the extant research on the use of bibliotherapy, and the use of library resources and services by mental health care staff, teachers, and patients in such facilities